Vocational Proficiency Education In Boarding Schools - Retno Anisa Larasati; Iim Wasliman; Hanafiah Hanafiah; Waska Warta (Syntax Corporation Indonesia, 2021)
The purpose of this research is to describe and describe, vocational proficiency education in Boarding Schools. Grand Teory in this study uses the theory from Terry (1958) dividing the four basic functions of management, namely Planning, Organizing, Actuating and Controlling. The results showed that vocational skills education in an effort to improve the entrepreneurial spirit in boarding schools is still not maximal. It is proven that only a few Boarding Schools graduates have an entrepreneurial spirit. Vocational proficiency education in boarding is more likely to provide theory than practice so that the learning stategi provided is less comprehensive, innovative, and creative.